(untitled) (Revista Archai, 2012)
P. Radici Colace, S. M. Medaglia, L. Rossetti, S. Sconocchia (ed.), Il Dizionario delle scienze e delle tecniche di Grecia e Roma, 2 vols., Pisa-Roma, Fabrizio Serra, 2010